Inovasi Pembelajaran Al-Islam Dan Kemuhammadiyahan Berbasis Merdeka Belajar Kampus Merdeka Untuk Peningkatan Soft Skill Mahasiswa - Sulaeman Sulaeman; Wahdania Wahdania; Siti Muthahharah; Habib Saputra (Journal on Education, 2023)
The independent campus learning policy (MBKM) requires changes to the curriculum and learning models in higher education, including Al-Islam and Kemuhammadiyahan (AIK) learning innovations at Muhammadiyah University (Unismuh) Makassar. There is a meeting point between the AIK Education Guidelines prepared by the PP Muhammadiyah Diktilitbang Council and the MBKM Program implemented by the Ministry of Education and Culture-Ristek of the Republic of Indonesia, namely that both require a learning model that is varied, fun, based on direct experience, contextual, and focused on needs. This study used descriptive qualitative method. Data was collected through observation, interviews and document analysis. The results of this research found that Al-Islam and Muhammadiyahan learning innovations based on the Merdeka Belajar Independent Campus at Unismuh Makassar were implemented in various forms and provided space for students to develop various soft skills such as discipline, honesty, empathy, social awareness, effective communication, cooperation, and problem solving skills.